Fear of Falling in Older Mexican Americans: A Longitudinal Study of Incidence and Predictive Factors. Issue 12 (26th October 2016) - Dierking, Leah; Markides, Kyriakos; Al Snih, Soham; Kristen Peek, M.
Abstract : Objectives: To determine predictors of fear of falling in older Mexican Americans over time. Design: Longitudinal study. Setting: Community‐dwelling residents throughout California, Colorado, New Mexico, Arizona, and Texas. Participants: Community‐dwelling Mexican Americans aged 72 and older participating in the Hispanic Established Populations for the Epidemiologic Study of the Elderly from 2000–01 to 2010–11 (N = 1, 682). Measurements: Fear of falling was measured at baseline and at each subsequent wave. Baseline demographic and clinical variables included social support, fall history, depression symptoms, Mini‐Mental State Examination (MMSE) score, activity of daily living (ADL) and instrumental ADL (IADL) limitations, and chronic health conditions. Results: Nine hundred fifty three (56.7%) subjects reported fear of falling at baseline, 262 of whom reported severe fear of falling. The predictors of reporting any fear of falling over time included female sex, frequent familial interaction, depression, chronic health conditions, IADL limitations, higher MMSE score, and three or more falls in the last 12 months. Predictors of severe fear of falling included older age, female sex, married, depressive symptoms, chronic health conditions, IADL limitations, higher MMSE score, and fall history. Protective factors included frequent friend interaction and higher levels of education. Conclusion: Fear of falling is prevalent in older Mexican‐American adults. The presence of friends nearby was shown to be protective against, whereas the presence of family nearby was shown to be predictive of fear of falling.